MEASUREMENT UNCERTAINTY OF THE OPTICAL WAVELENGTH CALIBRATION 633 nm BY BEAT FREQUENCY MEASUREMENT METHODS - Asep Hapiddin; Yulita Ika Pawestri; A. M. Boynawan; Ratnaningsih Ratnaningsih (LIPI Press, Anggota IKAPI, 2020)
Measurement traceability is one of the critical aspects in metrology area. The measurement uncertainty had been evaluated to assure reliability of the optical wavelength calibration system for stabilized He-Ne laser 633 nm in SNSU-BSN. Beat frequency measurement was applied as a calibration method by utilizing KIM-1 as a reference standard that traceable to SI unit through CCL-K11 key comparison. Best measurement capability declares with a relative uncertainty of ±1.3×10-10 by excluding UUC effect. The calibration replica was performed as a validation process, dual mode laser head Agilent 5519B took a role as UUC. As calibration result, beat frequency of KIM-1 and UUC is (122.931±0.060) MHz. Among all of the uncertainty sources, KIM-1 uncertainty most significant influence to the beat frequency uncertainty and the optical wavelength of the UUC laser in vacuum condition. Based on the evaluation result, the calibration system of stabilized He-Ne laser can be validated and trace back with documented unbroken calibration chain to the primary standard of length, KIM-1 where established in SNSU-BSN.